제습냉방시스템에서 요소성능이 시스템성능에 미치는 영향 - 장영수; 이대영 (대한설비공학회, 2007)
Cycle simulation is performed for two types of the desiccant cooling system incorporating a regenerative evaporative cooler. The cooling capacity and COP are evaluated at various effectiveness values of the regenerative evaporative cooler, the desiccant rotor and the sensible heat exchanger. As either of the effectiveness of the regenerative evaporative cooler or the humidity effectiveness of the desiccant rotor increases, both the cooling capacity and COP increase, but the enthalpy leak ratio gives the opposite effect on the system performance. It is found that COP of cycle A mainly depends on the humidity effectiveness of the desiccant rotor, while for cycle B enthalpy leak ratio of desiccant rotor has the major impact on COP. The effect of the sensible heat exchanger on the cooling capacity is small about 1/10 compared with those of other components.